GENERIC SCIENCE SKILLS: PHET APPLICATIONS BASED ON DISCOVERY LEARNING - Haryanto, Haryanto; Asrial, Asrial; Sanova, Aulia; Widowati, Atri; Saputra, Adhe (LPPM Universitas Jambi, 2024)
This pioneering research embarks on an ambitious quest to assess the conceptual, procedural feasibility, and efficacy of a groundbreaking educational intervention, the Discovery Learning model teaching module infused with the innovative PhET application aimed at enhancing students' generic skills proficiency in the domain of chemistry. In a departure from conventional methodologies, this study employs a rigorous Research and Development (R&D) framework underpinned by the renowned 4-D Model to craft and validate this transformative pedagogical tool meticulously. The research cohort comprises high school students and chemistry educators poised at the vanguard of educational innovation. Employing a meticulously designed set of validation and response questionnaires, the study harnesses the power of descriptive and inferential statistics to glean profound insights into the impact of the intervention. The findings illuminate a resounding success: the Discovery Learning model teaching module, seamlessly integrated with the PhET application, exhibits exceptional validity and practicality and yields tangible improvements in students' generic chemistry science skills. Moreover, the overwhelmingly positive feedback from both educators and students, coupled with discernible disparities in responses between the experimental and control groups, underscores the transformative potential of this cutting-edge educational tool. This research's novelty lies in its pioneering development and validation of a PhET application-based Discovery Learning module, heralding a paradigm shift in secondary school chemistry education with the promise of fostering a new generation of scientifically literate and adept learners primed to navigate the complexities of the modern world.